The "Voracity" and "Craving" Effects of Export Booms and Busts on Firm Bribery: Evidence from a Multi-level Empirical Analysis - Joël Cariolle (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
The evidence of a "voracity effect" of revenue windfalls reducing growth by fostering rent-seeking and corruption is widely documented by the literature. However, the reverse hypothesis of a "scarcity effect" of revenue downfalls, stimulating corruption by creating resource shortages, has theoretical foundations but little empirical support. This paper fills this gap by providing an empirical analysis of the voracity and scarcity effects of export booms and busts on firm bribery in developing countries. Exploiting 19,712 bribery reports from firms located in 36 developing countries, multilevel estimations of these effects are conducted. The results support a robust positive effect of both export booms and busts on bribery when democratic and financial institutions are weak. Conversely, a robust negative effect of booms and busts on bribery is evidenced when institutions are better off. Therefore, consistent with the literature, this paper provides additional evidence on the importance of institutional safeguards against corrupt practices in times of resource abundance. But more importantly, it provides new insights into their importance in times of shortage.Keywords: corruption, rent-seeking, export instability, booms, busts, financial markets, democracy, institutions
Keywords: 330; corruption; rent-seeking; export instability; booms; busts; financial markets; democracy; institutions